The Ethical and the Legal Aspects of Vulnerability in the Christian Perspective - Tzitzis, Stamatios (Studia Bioethica, 2012)
Anyone can experience harsh conditions of life that make him vulnerable. However, the idea of vulnerability is more suited for potentially individuals or groups that are socially disadvantaged and marginalized. Thus they need special attention and care from society. Postmodern humanism, based on personal dignity, gives special attention and legal protection to those who are vulnerable. Vulnerability means becoming aware of the “other” whose suffering existence calls for solidarity. A true ethic of vulnerability should not devalue the ontological status of man as a person. Christian philosophy improves and refines this ethic in the light of agape. In this perspective, vulnerability opens a relational space where the “otherness” commits its suffering in the full life of Christ. Life is participation in logos which is Christ personified, an affirmation of the human person created in the image of God. Therefore, euthanasia is inconsistent with agapeic affirmation of life. The ethics of vulnerability in Christian perspective, instead of reducing life to a question of individual rights, sees it ontologically and is therefore incompatible with any kind of negation of the person in the name of relief from suffering.